Selection of gonadotrophin surge attenuating factor phage antibodies by bioassay - Mason Helen D; Sorsa-Leslie Tarja; Harris William J; Fowler Paul A (BMC, 2005)
Abstract Background We aimed to combine the generation of "artificial" antibodies with a rat pituitary bioassay as a new strategy to overcome 20 years of difficulties in the purification of gonadotrophin surge-attenuating factor (GnSAF). Methods A synthetic single-chain antibody (Tomlinson J) phage display library was bio-panned with partially purified GnSAF produced by cultured human granulosa/luteal cells. The initial screening with a simple binding immunoassay resulted in 8 clones that were further screened using our in-vitro rat monolayer bioassay for GnSAF. Initially the antibodies were screened as pooled phage forms and subsequently as individual, soluble, single-chain antibody (scAbs) forms. Then, in order to improve the stability of the scAbs for immunopurification purposes, and to widen the range of labelled secondary antibodies available, these were engineered into full-length human immunoglobulins. The immunoglobulin with the highest affinity for GnSAF and a previously described rat anti-GnSAF polyclonal antiserum was then used to immunopurify bioactive GnSAF protein. The two purified preparations were electrophoresed on 1-D gels and on 7 cm 2-D gels (pH 4-7). The candidate GnSAF protein bands and spots were then excised for peptide mass mapping. Results Three of the scAbs recognised GnSAF bioactivity and subsequently one clone of the purified scAb-derived immunoglobulin demonstrated high affinity for GnSAF bioactivity, also binding the molecule in such as way as to block its bioactivity. When used for repeated immunopurification cycles and then Western blot, this antibody enabled the isolation of a GnSAF-bioactive protein band at around 66 kDa. Similar results were achieved using the rat anti-GnSAF polyclonal antiserum. The main candidate molecules identified from the immunopurified material by excision of 2-D gel protein spots was human serum albumin precursor and variants. Conclusion This study demonstrates that the combination of bioassay and phage display technologies is a powerful tool in the study of uncharacterised proteins that defy conventional approaches. In addition, we conclude that these data support suggestions that GnSAF may be structurally related to serum albumin or very tightly bound to serum albumin.